Tinjauan Yuridis Terhadap Putusnya Hubungan Perkawinan Akibat Perceraian yang Disebabkan oleh Perilaku Gemar Berjudi Ditinjau Berdasarkan Undang-Undang Perkawinan dan Hukum Islam - Adinda Firsta Deni Maharani; Djanuardi Djanuardi; Sherly Machmud Imam Slamet (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Divorce represents the dissolution of the marital bond between husband and wife within a household. Divorce can only occur when there are strong reasons justifying the decision. One reason that can lead to divorce, according to the Marriage Law and the Compilation of Islamic Law (KHI), is due to one party's addiction to gambling. This is reflected in the Batam Religious Court Decision Number 150/Pdt.G/2022/PA.Batam. This study aims to understand and analyze gambling as a reason for divorce, as well as the legal protection for the wife in a divorce caused by her husband's gambling addiction, based on the Marriage Law and the Compilation of Islamic Law (KHI). This research employs a normative juridical approach with descriptive analytical specifications. The research methods used in this study include library research and field research through interviews. The data analysis method employed is qualitative juridical analysis. The research results indicate that, first, the lawsuit in the Batam Religious Court Decision Number 150/Pdt.G/2022/PA.Batam is in accordance with the provisions of Article 19 letter a of the Government Regulation on the Implementation of the Marriage Law in conjunction with Article 116 letter a of the Compilation of Islamic Law (KHI). Second, as a preventive measure to protect the rights of the wife and children in a divorce caused by gambling addiction, the wife can include claims regarding custody and support for herself in the divorce petition. After the divorce decree is issued, the wife can also file a lawsuit regarding the division of marital property.